Studies on the Interactions of 3,11-Difluoro-6,8,13-trimethyl-8H-quino[4,3,2-kl]acridinium and Insulin with the Quadruplex-Forming Oligonucleotide Sequence a2 from the Insulin-Linked Polymorphic Region - Peter Jonas Wickhorst (MDPI AG, 2021)
Recently, several quadruplex-DNA-forming sequences have been identified in the insulin-linked polymorphic region (ILPR), which is a guanine-rich oligonucleotide sequence in the promoter region of insulin. The formation of this non-canonical quadruplex DNA (G4-DNA) has been shown to be involved in the biological activity of the ILPR, specifically with regard to its interplay with insulin. In this context, this contribution reports on the investigation of the association of the quadruplex-forming ILPR sequence a2 with insulin as well as with the well-known G4-DNA ligand 3,11-difluoro-6,8,13-trimethyl-8H-quino[4,3,2-kl]acridinium (1), also named RHPS4, by optical and NMR spectroscopy. CD- and NMR-spectroscopic measurements confirmed the preferential formation of an antiparallel quadruplex structure of a2 with four stacked guanine quartets. Furthermore, ligand 1 has high affinity toward a2 and binds by terminal π stacking to the G1–G11–G15–G25 quartet. In addition, the spectroscopic studies pointed to an association of insulin to the deoxyribose backbone of the loops of a2.